Intra and interspecific variability of Quercus suber and Quercus canariensis, an intrinsic water-use efficiency approach for differentiation - Olfa Frouja; Majdi Hammami; Sarra Dakhlaoui; Wissem Aidi Wannes; Kamel Hessini; Kamel Msaada; Hela Ben Ahmed (Environmental Research Communications, 2022)
In Tunisia, the oak forest is essentially restricted to the north-west (Kroumirie and Mogods), which is the wettest zone of the country. It forms ecosystems of great ecological and socio-economic interest. This is a significant source of income for local population. In addition, it contributes to soil conservation and is home to a rich and diversified fauna and flora and offers the region a picturesque landscape. This precious and fragile forest capital is currently threatened under the effect of various pressures, mainly the browsing of young plants being reconstituted and vegetative competition regarding resources of the environment. Hence the interest in studying the intra and interspecific variability of the oak, this study is essentially based on the morphological and physiological comparison of the two species of oak, Quercus suber and Quercus canariensis with their cohabitation in the same area, this variability was carried out by multivariate biostatistical analyzes using a set of data including morphological traits, isotopic analysis of the leaves, water use efficiency, as well as the phenolic composition and antioxidant activities of the leaves extracts. The results showed that leaf morphology and water use efficiency are discriminating factors for differentiation to choose the right specie that will be used for reforestation. The Q. canariensis specie growing in the Bni Mtir region was characterized by a high intrinsic water-use efficiency and high biomass recovery. These results let us suppose that Q. canariensis was the perfect specie for reforestation given its ability to produce a large amount of biomass with less water, which is what environmentalists demand.